Corrugated plate SCR (Selective Catalytic Reduction) denitration catalyst substrate as well as preparation method and use method thereof
By punching the fiberglass fiberboard and coating the slurry with a substrate of butyl titanate and other components, the problem of easy falling off of the active substance of the corrugated plate catalyst is solved, and the anti-shrink performance and service life are improved.
Patent Information
- Application Number
- CN202310697097.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-13
AI Technical Summary
In actual application, the active substances are prone to fall off and have insufficient anti-shrink performance, which affects the overall performance and service life of the catalyst.
Using glass fiberboard as the substrate, and the preparation of slurry is made by punching and coating the substrate, including butyl titanate, ethyl orthosilicate, silica sol and polyvinyl alcohol, to form a strong substrate The coating layer improves the adhesion firmness and anti-shrink properties of the active substance.
It significantly improves the firmness and anti-shrink performance of the catalyst active substance, extends the service life of the catalyst, and ensures the stable operation of the device.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of SCR denitration catalysts and relates to a corrugated plate SCR denitration catalyst substrate and a preparation method and a use method thereof. Background Art
[0002] Nitrogen oxides (NO x ) is one of the main pollutants in the atmospheric environment, which not only causes environmental problems such as haze, acid rain, and photochemical smog, but also has adverse effects on human health. x The removal technology is the selective catalytic reduction (SCR) method, which has high denitration efficiency and no secondary pollution. Its core is the denitration catalyst. According to the catalyst processing and molding method, the catalyst is mainly divided into honeycomb, corrugated plate and plate type. Honeycomb catalysts are widely used in the market. Due to the light weight, large geometric specific surface area and short production cycle of corrugated plate catalysts, they also occupy a certain market share.
[0003] The substrate disclosed in patent CN201810166192.1 is composed of 53% to 56% SiO2, 27% to 30% CaO, 12% to 15% Al2O3, and 1% to 3% MgO by mass percentage. The invention prepares a substrate that meets the requirements of corrugated plate catalysts by adjusting the corrugation forming control technology. Although the substrate meets the requirements of corrugated plate catalyst preparation, the active material still has the problem of easy shedding during actual application, and the anti-scouring performance needs to be further improved.
[0004] Patent CN201110321163.6 uses stainless steel plate, stainless steel mesh, titanium plate or titanium mesh as the substrate, and uses electroplating, coating or pressing to attach the carrier and active components. First, the catalyst carrier (titanium dioxide) is attached to the processed corrugated skeleton, and then the active components are attached to it. The catalyst substrate prepared by this process is light in weight, has a large specific surface area of the catalyst, is not easy to accumulate dust, and the adhesion firmness of the active substance on the substrate has greater room for improvement.
[0005] The catalyst preparation process of patent CN201611002886.9 uses inorganic fiberboard as the substrate, and evenly sprays the active sol prepared with vanadium pentoxide, molybdenum trioxide, tungsten trioxide, titanium dioxide and other substances on the upper and lower surfaces of the inorganic fiberboard, and rolls it into a corrugated shape to obtain a finished catalyst. The catalyst prepared using this substrate and process has the advantages of low cost, short time, high activity and high wear resistance. The inorganic fiberboard is aluminosilicate fiberboard, quartz fiberboard or boron fiberboard. The substrate has not been treated or improved, and there is a problem that the active substance is easy to fall off, which affects the overall performance of the catalyst.
[0006] Corrugated plate catalysts are mainly coated catalysts, which are usually prepared by coating active substances on a substrate, drying and calcining. The substrate of commercial corrugated plate catalysts is mainly glass fiber. During use, due to the particulate matter and large amount of flue gas in the flue gas, it is easy to cause the active substances to fall off the substrate, which in turn causes the denitration performance of the catalyst to decline, seriously affecting the stable and standard operation of the device.
[0007] Therefore, in order to improve the overall performance of corrugated plate deNOx catalysts, it is of great significance to develop a substrate suitable for corrugated plate catalysts based on the substrate structure, preparation process and active substances. Summary of the invention
[0008] The object of the present invention is to provide a corrugated plate SCR denitration catalyst substrate and a preparation method and a use method thereof. The corrugated plate SCR denitration catalyst substrate and the preparation method thereof can improve the firmness of the catalyst active substance coated on the substrate and effectively ensure the normal service life of the catalyst.
[0009] To achieve the above-mentioned purpose, the present invention provides a corrugated plate SCR denitration catalyst substrate, which is mainly composed of a glass fiber board and a substrate coating slurry. The substrate coating slurry includes the following component raw materials by weight: 20% to 55% of butyl titanate, 10% to 40% of tetraethyl orthosilicate, 5% to 25% of silica sol, 1% to 10% of polyvinyl alcohol, 10% to 40% of anhydrous ethanol and 5% to 20% of deionized water.
[0010] The corrugated plate SCR denitration catalyst substrate of the present invention, preferably, the substrate coating slurry includes the following component raw materials in weight content: 25% to 50% of butyl titanate, 15% to 30% of tetraethyl orthosilicate, 10% to 20% of silica sol, 3% to 7% of polyvinyl alcohol, 10% to 30% of anhydrous ethanol, and 10% to 15% of deionized water.
[0011] The present invention also provides a method for preparing a corrugated plate SCR denitration catalyst substrate, the preparation method comprising the following steps:
[0012] (1) According to the design of corrugated plate catalyst, punching treatment is performed on the glass fiber plate;
[0013] (2) preparing a pretreatment solution, comprising the following raw materials by weight: 35% to 65% methanol, 20% to 40% silane, 5% to 30% acetic acid, and 2% to 15% deionized water;
[0014] (3) placing the glass fiber board punched in step (1) in the pretreatment solution prepared in step (2) for immersion;
[0015] (4) drying the glass fiber board impregnated in step (3) and corrugating the board by pressing rollers;
[0016] (5) bonding and assembling the glass fiber boards treated in step (3) and step (4) to obtain a glass fiber substrate precursor;
[0017] (6) adding butyl titanate to anhydrous ethanol;
[0018] (7) adding tetraethyl orthosilicate to the solution of step (6) to form a suspension;
[0019] (8) adding silica sol to the suspension of step (7) to form a mixed suspension;
[0020] (9) adding polyvinyl alcohol to the mixed suspension of step (8) to obtain a coating slurry for the corrugated board substrate;
[0021] (10) The substrate coating slurry obtained in step (9) is coated on the glass fiber substrate precursor in step (5), and dried to obtain a corrugated plate SCR denitration catalyst substrate.
[0022] In the method for preparing the corrugated plate SCR denitration catalyst substrate of the present invention, preferably, in step (1), the thickness of the glass fiber board is 0.4-1 mm, the diameter of the punched holes is 0.5-3 mm, and the spacing between the holes is 50-100 mm.
[0023] In the method for preparing the corrugated plate SCR denitration catalyst substrate of the present invention, preferably, in step (2), the pretreatment liquid comprises the following component raw materials in weight content: methanol 40% to 60%, silane 25% to 35%, acetic acid 10% to 25%, and deionized water 5% to 10%.
[0024] In the method for preparing the corrugated plate SCR denitration catalyst substrate of the present invention, preferably, in step (3), the immersion temperature is 40 to 50° C., and the immersion time is 60 to 80 minutes.
[0025] In the method for preparing the corrugated plate SCR denitration catalyst substrate of the present invention, preferably, in step (4), the temperature of the corrugation forming is 250-300°C.
[0026] In the method for preparing the corrugated plate SCR denitration catalyst substrate of the present invention, preferably, in step (7), the pH is adjusted to 2-4.
[0027] In the method for preparing the corrugated plate SCR denitration catalyst substrate of the present invention, preferably, in step (8), during the process of adding the silica sol to the suspension of step (7), the suspension is stirred at a uniform speed and heated to 70-80°C.
[0028] In the method for preparing the corrugated plate SCR denitration catalyst substrate of the present invention, preferably, in step (9), during the process of adding polyvinyl alcohol to the mixed suspension solution of step (8), deionized water is added, stirred at a uniform speed, and heated to 90-95°C.
[0029] In the method for preparing the corrugated plate SCR denitration catalyst substrate of the present invention, preferably, in step (10), the drying temperature is 50 to 60° C., and the drying time is 30 to 60 minutes.
[0030] The present invention also provides a method for using a corrugated plate SCR denitration catalyst substrate, which comprises: coating an active substance on the corrugated plate SCR denitration catalyst substrate, and then drying and calcining to obtain the corrugated plate denitration catalyst.
[0031] The corrugated plate SCR denitration catalyst substrate of the present invention has strong anti-scouring performance. After coating the active substance, the active substance is not easy to fall off, which can improve the firmness of the catalyst active substance on the substrate, thereby extending the service life of the catalyst and ensuring the stable operation of the device for a longer period of time.
[0032] The corrugated plate SCR denitration catalyst substrate provided by the present invention is subjected to punching treatment for substrate coating slurry coating. The pretreatment liquid can effectively remove impurities on the surface of the glass fiber board, improve the performance of the glass fiber board, and is conducive to corrugation forming and the adhesion of the substrate coating slurry. The substrate coating slurry prepared by butyl titanate, tetraethyl orthosilicate, anhydrous ethanol, silica sol and polyvinyl alcohol has good adhesion and permeability and can be evenly dispersed on the surface of the glass fiber board. Under the action of chemical bonds such as Ti-O-Ti bonds, Si-O-Si bonds, and Ti-O-Si bonds, the substrate coating slurry forms a whole and is wrapped on the surface of the glass fiber board. In particular, after the glass fiber board is punched, the slurry on the front and back of the glass fiber board is embedded together through the grid holes. Under the action of chemical bonds, the bonding force between the substrate coating slurry and the glass fiber board is greatly improved, and the firmness of the substrate coating slurry on the glass fiber board is improved, and the overall stability of the coating is ensured, thereby enhancing the anti-scouring performance. In addition, in the later stage of catalyst preparation, the substrate coating slurry is dried and calcined to form titanium dioxide, which is an important carrier of the active substance and is also conducive to the coating of the active substance on the substrate surface. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is described in detail below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the implementation of the present invention, rather than all the embodiments.
[0034] Test conditions: airspeed 6000h -1 , reaction temperature 350℃, particle size 500~600mg / Nm3 , N2 is the balance gas, NO x 350~450mg / Nm 3 , O2 1.5~2.0%, H2O 5~10%.
[0035] Shedding rate = (total mass of catalyst - mass of catalyst after shedding test) / mass of coating layer × 100%.
[0036] The catalyst prepared from the glass fiber board without any treatment had an active substance shedding rate of 21.5%.
[0037] Embodiment 1:
[0038] A glass fiber board with a thickness of 0.5 mm is punched to obtain a hole with a diameter of 1 mm and a hole spacing of 50 mm; a pretreatment solution is prepared comprising the following raw materials by weight: 45% methanol, 30% silane, 15% acetic acid and 10% deionized water; the punched glass fiber board is immersed in the pretreatment solution at a temperature of 45° C. for 60 minutes; after the impregnated glass fiber board is dried, corrugation is performed using a pair of pressing rollers at a temperature of 280° C.; and the glass fiber board immersed in the pretreatment solution and the corrugated glass fiber board formed by the pair of pressing rollers are assembled to obtain a glass fiber substrate precursor. Add 40g of butyl titanate to 35g of anhydrous ethanol and stir evenly to obtain a solution; continue to add 25g of ethyl orthosilicate to the above solution, stir at a uniform speed to form a suspension, and adjust the pH to 3; then add 15g of silica sol to the above suspension, stir at a uniform speed, and heat to 70°C to obtain a mixed suspension; continue to add 5g of polyvinyl alcohol to the above mixed suspension, and at the same time add 15g of deionized water, stir at a uniform speed, and heat to 90°C to obtain a corrugated board substrate coating slurry. Finally, the substrate coating slurry is applied to the assembled glass fiber substrate precursor, and dried at a temperature of 50°C for 30 minutes to obtain a corrugated board SCR denitration catalyst substrate.
[0039] The prepared active substance is coated on the corrugated plate SCR denitration catalyst substrate, dried and calcined to obtain the corrugated plate denitration catalyst. The active substance shedding rate is calculated to be 6.7% after flue gas flushing.
[0040] Comparative Example 1:
[0041] Take a glass fiber board with a thickness of 0.5 mm; prepare a pretreatment solution including the following raw materials by weight: 45% methanol, 30% silane, 15% acetic acid, and 10% deionized water; immerse the punched glass fiber board in the pretreatment solution at a temperature of 45° C. for 60 minutes; after the impregnated glass fiber board is dried, corrugation is performed using a pair of pressing rollers at a temperature of 280° C.; then, the glass fiber board impregnated with the pretreatment solution and the corrugated glass fiber board formed by the pair of pressing rollers are assembled to obtain a glass fiber substrate precursor. Add 40g of butyl titanate to 35g of anhydrous ethanol and stir evenly to obtain a solution; continue to add 25g of ethyl orthosilicate to the above solution, stir at a uniform speed to form a suspension, and adjust the pH to 3; then add 15g of silica sol to the above suspension, stir at a uniform speed, and heat to 70°C to obtain a mixed suspension; continue to add 5g of polyvinyl alcohol to the above mixed suspension, and at the same time add 15g of deionized water, stir at a uniform speed, and heat to 90°C to obtain a corrugated board substrate coating slurry. Finally, the substrate coating slurry is applied to the assembled glass fiber substrate precursor, and dried at a temperature of 50°C for 30 minutes to obtain a corrugated board SCR denitration catalyst substrate.
[0042] The prepared active substance is coated on the corrugated plate SCR denitration catalyst substrate, dried and calcined to obtain the corrugated plate denitration catalyst. The active substance shedding rate is calculated to be 15.8% after flue gas flushing.
[0043] Embodiment 2:
[0044] A glass fiber board with a thickness of 0.7 mm is punched to obtain a hole with a diameter of 2 mm and a hole spacing of 80 mm; a pretreatment solution is prepared comprising the following component raw materials by weight: 50% methanol, 35% silane, 10% acetic acid and 5% deionized water; the punched glass fiber board is immersed in the pretreatment solution at a temperature of 40° C. for 80 min; after the impregnation is completed, the glass fiber board is dried and corrugated by a pressing roller at a temperature of 300° C.; the glass fiber board immersed in the pretreatment solution and the corrugated glass fiber board formed by the pressing roller are assembled to obtain a glass fiber substrate precursor. Add 45g of butyl titanate to 35g of anhydrous ethanol and stir evenly to obtain a solution; continue to add 35g of ethyl orthosilicate to the above solution, stir at a uniform speed to form a suspension, and adjust the pH to 4; then add 25g of silica sol to the above suspension, stir at a uniform speed, and heat to 80°C to obtain a mixed suspension; continue to add 6g of polyvinyl alcohol to the above mixed suspension, and at the same time add 20g of deionized water, stir at a uniform speed, and heat to 95°C to obtain a corrugated board substrate coating slurry. Finally, the substrate coating slurry is applied to the assembled glass fiber substrate precursor, and dried at a temperature of 55°C for 50 minutes to obtain a corrugated board SCR denitration catalyst substrate.
[0045] The prepared active substance is coated on the corrugated plate SCR denitration catalyst substrate, dried and calcined to obtain the corrugated plate denitration catalyst. The active substance shedding rate is calculated to be 6.4% after flue gas flushing.
[0046] Comparative Example 2:
[0047] A glass fiber board with a thickness of 0.7 mm is punched to obtain a hole with a diameter of 2 mm and a hole spacing of 80 mm; a pretreatment solution is prepared comprising the following component raw materials by weight: 50% methanol, 35% silane, 10% acetic acid and 5% deionized water; the punched glass fiber board is immersed in the pretreatment solution at a temperature of 40° C. for 80 min; after the impregnation is completed, the glass fiber board is dried and corrugated by a pressing roller at a temperature of 300° C.; the glass fiber board immersed in the pretreatment solution and the corrugated glass fiber board formed by the pressing roller are assembled to obtain a glass fiber substrate precursor. Add 45g of butyl titanate to 35g of anhydrous ethanol, stir evenly to obtain a solution; add 25g of silica sol to the above solution, stir evenly, and heat to 80°C to obtain a mixed suspension; continue to add 6g of polyvinyl alcohol to the above mixed suspension, and add 20g of deionized water at the same time, stir evenly, and heat to 95°C to obtain a corrugated board substrate coating slurry. Finally, the substrate coating slurry is applied to the assembled glass fiber substrate precursor, and dried at a temperature of 55°C for 50 minutes to obtain a corrugated board SCR denitration catalyst substrate.
[0048] The prepared active substance is coated on the corrugated plate SCR denitration catalyst substrate, dried and calcined to obtain the corrugated plate denitration catalyst. The active substance shedding rate is calculated to be 11.4% after flue gas flushing.
[0049] Embodiment 3:
[0050] A glass fiber board with a thickness of 0.8 mm is punched to obtain a hole diameter of 3 mm and a hole spacing of 100 mm; a pretreatment solution comprising the following component raw materials by weight is prepared: 55% methanol, 30% silane, 10% acetic acid and 5% deionized water; the punched glass fiber board is immersed in the pretreatment solution at a temperature of 50° C. for 70 min; after the impregnated glass fiber board is dried, corrugation is performed using a pair of pressing rollers at a temperature of 280° C.; and then the glass fiber board immersed in the pretreatment solution and the corrugated glass fiber board formed by the pair of pressing rollers are assembled to obtain a glass fiber substrate precursor. Add 50g of butyl titanate to 45g of anhydrous ethanol and stir evenly to obtain a solution; continue to add 35g of ethyl orthosilicate to the above solution, stir at a uniform speed to form a suspension, and adjust the pH to 2; then add 35g of silica sol to the above suspension, stir at a uniform speed, and heat to 75°C to obtain a mixed suspension; continue to add 10g of polyvinyl alcohol to the above mixed suspension, and add 20g of deionized water at a uniform speed, stir at a uniform speed, and heat to 90°C to obtain a corrugated board substrate coating slurry. Finally, the substrate coating slurry is applied to the assembled glass fiber substrate precursor, and dried at a temperature of 60°C for 60 minutes to obtain a corrugated board SCR denitration catalyst substrate.
[0051] The prepared active substance is coated on the corrugated plate SCR denitration catalyst substrate, dried and calcined to obtain the corrugated plate denitration catalyst. The active substance shedding rate is calculated by flue gas flushing to be 9.3%.
[0052] Comparative Example 3:
[0053] Take a glass fiber board with a thickness of 0.8 mm and punch it. The hole diameter is 3 mm and the hole spacing is 100 mm. The glass fiber board is corrugated at a temperature of 280°C using a pair of rollers. Then assemble the glass fiber board and the corrugated glass fiber board formed by the pair of rollers to obtain a glass fiber substrate precursor. Add 50g of butyl titanate to 45g of anhydrous ethanol and stir evenly to obtain a solution. Continue to add 35g of ethyl orthosilicate to the above solution, stir at a uniform speed to form a suspension, and adjust the pH to 2; then add 35g of silica sol to the above suspension, stir at a uniform speed, and heat to 75°C to obtain a mixed suspension; continue to add 10g of polyvinyl alcohol to the above mixed suspension, and add 20g of deionized water at the same time, stir at a uniform speed, and heat to 90°C to obtain a corrugated board substrate coating slurry. Finally, the substrate coating slurry is applied to the assembled glass fiber substrate precursor, and dried at a temperature of 60°C for 60min to obtain a corrugated board SCR denitration catalyst substrate.
[0054] The prepared active substance is coated on the corrugated plate SCR denitration catalyst substrate, dried and calcined to obtain the corrugated plate denitration catalyst. The active substance shedding rate is calculated to be 16.7% after flue gas flushing.
[0055] Embodiment 4:
[0056] A glass fiber board with a thickness of 1 mm is punched to obtain a hole with a diameter of 2 mm and a hole spacing of 60 mm; a pretreatment solution is prepared comprising the following raw materials by weight: 50% methanol, 25% silane, 18% acetic acid and 7% deionized water; the punched glass fiber board is immersed in the pretreatment solution at a temperature of 50°C for 80 minutes; after the impregnated glass fiber board is dried, corrugation is performed using a pair of pressing rollers at a temperature of 300°C; and then the glass fiber board immersed in the pretreatment solution and the corrugated glass fiber board formed by the pair of pressing rollers are assembled to obtain a glass fiber substrate precursor. Add 48g of butyl titanate to 50g of anhydrous ethanol and stir evenly to obtain a solution; continue to add 32g of ethyl orthosilicate to the above solution, stir at a uniform speed to form a suspension, and adjust the pH to 3; then add 27g of silica sol to the above suspension, stir at a uniform speed, and heat to 80°C to obtain a mixed suspension; continue to add 8g of polyvinyl alcohol to the above mixed suspension, and add 27g of deionized water at a uniform speed, stir at a uniform speed, and heat to 95°C to obtain a corrugated board substrate coating slurry. Finally, the substrate coating slurry is applied to the assembled glass fiber substrate precursor, and dried at a temperature of 60°C for 50 minutes to obtain a corrugated board SCR denitration catalyst substrate.
[0057] The prepared active substance is coated on the corrugated plate SCR denitration catalyst substrate, dried and calcined to obtain the corrugated plate denitration catalyst. The active substance shedding rate is calculated to be 6.5% after flue gas flushing.
[0058] Comparative Example 4:
[0059] A glass fiber board with a thickness of 1 mm is punched to obtain a hole diameter of 2 mm and a hole spacing of 60 mm; a pretreatment solution including the following component raw materials by weight is prepared: 50% methanol, 25% silane, 18% acetic acid and 7% deionized water; the punched glass fiber board is immersed in the pretreatment solution at a temperature of 50°C for 80 minutes; after the impregnated glass fiber board is dried, corrugation is performed using a pair of pressing rollers at a temperature of 300°C; and then the glass fiber board immersed in the pretreatment solution and the corrugated glass fiber board formed by the pair of pressing rollers are assembled to obtain a glass fiber substrate precursor. Add 32g of ethyl orthosilicate to 50g of anhydrous ethanol, stir at a constant speed to obtain a solution, and adjust the pH to 3; add 27g of silica sol to the above solution, stir at a constant speed, and heat to 80°C to obtain a suspension; continue to add 8g of polyvinyl alcohol to the above suspension, and add 27g of deionized water at a constant speed, stir at a constant speed, and heat to 95°C to obtain a corrugated board substrate coating slurry. Finally, the substrate coating slurry is applied to the assembled glass fiber substrate precursor, and dried at a temperature of 60°C for 50 minutes to obtain a corrugated board SCR denitration catalyst substrate.
[0060] The prepared active substance is coated on the corrugated plate SCR denitration catalyst substrate, dried and calcined to obtain the corrugated plate denitration catalyst. The active substance shedding rate is calculated to be 16.3% after flue gas flushing.
[0061] The results of the examples and comparative examples show that the punching treatment of the glass fiber board, the pretreatment liquid, and the substrate coating slurry will cause changes in the shedding of active substances on the substrate to varying degrees, and jointly promote the change of the anti-scouring performance. Compared with the comparative example, the corrugated plate catalyst obtained by using the component raw materials and preparation process in the example has better anti-scouring performance.
[0062] In summary, the glass fiber substrate prepared by glass fiber board and substrate coating slurry can solve the problem of easy shedding of active substances in corrugated plate catalysts, improve the anti-scouring performance of the catalyst, and extend the service life of the catalyst.
[0063] The present invention is not limited to the aforementioned specific embodiments, and any changes or modifications made by any technician in the field of the present invention are all covered by the patent scope of the present invention.
Claims
1. A corrugated plate SCR denitration catalyst substrate, characterized in that: The invention is mainly composed of a glass fiber board and a substrate coating slurry, wherein the substrate coating slurry comprises the following component raw materials in weight content: 20% to 55% of butyl titanate, 10% to 40% of tetraethyl orthosilicate, 5% to 25% of silica sol, 1% to 10% of polyvinyl alcohol, 10% to 40% of anhydrous ethanol and 5% to 20% of deionized water.
2. The corrugated plate SCR denitration catalyst substrate according to claim 1, characterized in that: The substrate coating slurry comprises the following raw materials by weight: 25% to 50% butyl titanate, 15% to 30% ethyl orthosilicate, 10% to 20% silica sol, 3% to 7% polyvinyl alcohol, 10% to 30% anhydrous ethanol and 10% to 15% deionized water.
3. A method for preparing a corrugated plate SCR denitration catalyst substrate according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) According to the design of corrugated plate catalyst, punching treatment is performed on the glass fiber plate; (2) preparing a pretreatment solution, comprising the following raw materials by weight: 35% to 65% methanol, 20% to 40% silane, 5% to 30% acetic acid, and 2% to 15% deionized water; (3) placing the glass fiber board punched in step (1) in the pretreatment solution prepared in step (2) for immersion; (4) drying the glass fiber board impregnated in step (3) and corrugating the board by pressing rollers; (5) bonding and assembling the glass fiber boards treated in step (3) and step (4) to obtain a glass fiber substrate precursor; (6) adding butyl titanate to anhydrous ethanol; (7) adding tetraethyl orthosilicate to the solution of step (6) to form a suspension; (8) adding silica sol to the suspension of step (7) to form a mixed suspension; (9) adding polyvinyl alcohol to the mixed suspension of step (8) to obtain a coating slurry for the corrugated board substrate; (10) The substrate coating slurry obtained in step (9) is coated on the glass fiber substrate precursor in step (5), and dried to obtain a corrugated plate SCR denitration catalyst substrate.
4. The preparation method according to claim 3, characterized in that: In step (1), the thickness of the glass fiber board is 0.4-1 mm, the diameter of the punched holes is 0.5-3 mm, and the spacing between the holes is 50-100 mm.
5. The preparation method according to claim 3, characterized in that: In step (2), the pretreatment solution comprises the following raw materials by weight: 40% to 60% methanol, 25% to 35% silane, 10% to 25% acetic acid, and 5% to 10% deionized water.
6. The preparation method according to claim 3, characterized in that: In step (3), the immersion temperature is 40 to 50° C., and the immersion time is 60 to 80 minutes.
7. The preparation method according to claim 3, characterized in that: In step (4), the temperature of the corrugation forming is 250-300°C.
8. The preparation method according to claim 3, characterized in that: In step (7), the pH is adjusted to 2-4.
9. The preparation method according to claim 3, characterized in that: In step (8), the silica sol is added to the suspension of step (7) while being stirred at a constant speed and heated to 70-80°C.
10. The preparation method according to claim 3, characterized in that: In step (9), during the process of adding polyvinyl alcohol to the mixed suspension solution of step (8), deionized water is added, stirred at a constant speed, and heated to 90-95°C.
11. The preparation method according to claim 3, characterized in that: In step (10), the drying temperature is 50 to 60° C., and the drying time is 30 to 60 minutes.
12. A method for using the corrugated plate SCR denitration catalyst substrate according to any one of claims 1 to 2, characterized in that: include: The corrugated plate SCR denitration catalyst substrate is coated with an active substance, and then dried and calcined to obtain the corrugated plate denitration catalyst.
Citation Information
Patent Citations
SCR denitration catalyst and preparation method thereof
CN101185886A
Method for preparing vanadium-titanium supported stainless steel plate catalyst for flue gas denitration
CN102389805A
Preparation method of wool laser punched hollow fabric
CN105506954A
Polyvinyl alcohol / nano-silicon dioxide-titanium hybrid membrane and preparation method thereof
CN107233802A
Lightweight low-temperature SCR denitration catalyst and preparation method thereof
CN114682251A
Cited By
Preparation method of medium-temperature corrugated plate SCR (Selective Catalytic Reduction) denitration catalyst
CN121103348A
